A modified gentle human touch (GHT) to increase oxygen saturation levels on low birth weight infants: A study at a Private and Public Hospital in Central Java, Indonesia - Agi Yulia Riadini; Agus Suwandono; Runjati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Low birth weight (LBW) care in hospitals often causes discomfort and stress which affect changes in physiological function. Modification of gentle human touch with the left lateral position is described as a treatment for developmental care that supports the comfort and supportive position of the lungs which is expected to have a positive effect on oxygen saturation and respiratory frequency for infants.Aims: This study aimed to find the effect of gentle human touch modification with a left lateral position on oxygen saturation in LBW infants.Methods: This study used a quasi-experimental design study. The population in this study was 36 LBW babies who received care, selected at a private and public hospital in Central Java, Indonesia, using a consecutive sampling technique. The infants were then divided equally to: (i) a group who received a standard human touch given at the hospital, with a supine position (control), and (ii) a group where the infants have been provided with a modified gentle human touch with left lateral position (intervention). The statistical test used was Mann Whitney and Wilcoxon test.Results: From this study, it is acknowledged that modification gentle human touch with the left lateral position was more effective in increasing oxygen saturation than the control group when viewed from clinical changes. The oxygen saturation levels after intervention reached 98 to 99%. However, from the statistical analysis, it has been noted that the mean difference between the two groups is not significantly different at a level of 0.05.Conclusions: A modified gentle human touch with the left lateral position proposed in this study presents a positive contribution to the oxygen saturation of low birth weight infants. Thus, the findings may recommend the modification as a procedure in a hospital care unit for low birth weight infants at hospitals or at home. Keywords: Gentle human touch, Left lateral position, Low birth weight babies, Oxygen saturation. Received: 25 August 2018, Reviewed: 04 September 2018, Received: in revised form 26, February 2019, Accepted: 28 February 2019 DOI: 10.35898/ghmj-31549